2016
DOI: 10.1097/mnh.0000000000000297
|View full text |Cite
|
Sign up to set email alerts
|

Role of corin in the regulation of blood pressure

Abstract: Purpose of review Corin is a transmembrane protease that activates atrial natriuretic peptide (ANP), an important hormone in regulating salt-water balance and blood pressure. This review focuses on the regulation of corin function and potential roles of corin defects in hypertensive, heart, and renal diseases. Recent findings Proprotein convertase subtilisin/kexin-6 has been identified as a primary enzyme that converts zymogen corin to an active protease. Genetic variants that impair corin intracellular traf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 94 publications
0
28
0
Order By: Relevance
“…Examining disease linkage, Corin expression, which is quite specific to the cortical nephron-specific cell population, encodes a serine peptidase critical to the regulation of blood volume and blood pressure. Human variants in Corin are linked to hypertension, cardiac hypertrophy and pre-eclampsia (Li et al, 2017).…”
Section: Spatial and Temporal Diversity Of Nephron Cellsmentioning
confidence: 99%
“…Examining disease linkage, Corin expression, which is quite specific to the cortical nephron-specific cell population, encodes a serine peptidase critical to the regulation of blood volume and blood pressure. Human variants in Corin are linked to hypertension, cardiac hypertrophy and pre-eclampsia (Li et al, 2017).…”
Section: Spatial and Temporal Diversity Of Nephron Cellsmentioning
confidence: 99%
“…Corin is a trypsin-like serine protease that activates natriuretic peptides ( Cui et al, 2012 ; Li et al, 2017 ; Yan et al, 2000 ). It consists of a cytoplasmic tail, a transmembrane domain and an extracellular region with multiple protein modules and a C-terminal protease domain ( Hooper et al, 2000 ; Yan et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although it was not detected in the present study, several researches in vivo and in vitro have demonstrated that excessive fluid volume would cause cardiomyocyte injury and apoptosis, which could induce a series of cardiovascular dysfunctions by impairing biochemical signal transduction, vascular tone adaptation, and baroreflex control of circulation . When HD patients are fluid overloaded, the sustained preload‐induced cardiomyocyte injury might lead to abnormal expression and production of bioactive substances that could disrupt BP regulation . However, the exact mechanism involved was not yet adequately established.…”
Section: Discussionmentioning
confidence: 66%